2018
DOI: 10.4317/medoral.22237
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of Methylprednisolone Acetate, Sodium Hyaluronate and Tenoxicam in the treatment of non-reducing disc displacement of the temporomandibular joint

Abstract: BackgroundThis clinical study aimed to radiologically and clinically compare the effect of intra-articular injection of methylprednisolone, sodium hyaluronate or tenoxicam following arthrocentesis with that of arthrocentesis alone in patients with non-reducing disc displacement.Material and MethodsA total of 44 patients radiographically diagnosed with non-reducing disc displacement of the temporomandibular joint (TMJ) were randomly divided into four treatment groups, as follows: Group 1, arthrocentesis alone; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 28 publications
0
41
0
1
Order By: Relevance
“…However, the authors reported no statistically significant difference in pain or MMO between the two groups at any time intervals ( P ‐values not reported). Yavuz et al 18 conducted a similar trial with two additional groups of methylprednisolone and sodium hyaluronate. The authors reported significant improvement in pain and MMO for all groups ( P < .05).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the authors reported no statistically significant difference in pain or MMO between the two groups at any time intervals ( P ‐values not reported). Yavuz et al 18 conducted a similar trial with two additional groups of methylprednisolone and sodium hyaluronate. The authors reported significant improvement in pain and MMO for all groups ( P < .05).…”
Section: Resultsmentioning
confidence: 99%
“…15 A total of nine studies were included in this systematic review. 10,[16][17][18][19][20][21][22][23] Details of the included studies are presented in Table 1. The sample size of the trials varied from seven to a maximum of 20 patients per arm.…”
Section: Re Sultsmentioning
confidence: 99%
See 3 more Smart Citations